CO2 Capture With Absorbents of Tertiary Amine Functionalized Nano–SiO2 - Lai, Nanjun; Zhu, Qingru; Qiao, Dongyu; Chen, Ke; Tang, Lei; Wang, Dongdong; He, Wei; Chen, Yuemei; Yu, Tong (Frontiers in Chemistry, 2020)
To improve CO2 adsorption performance of nanoparticle absorbents, a novel tertiary amine functionalized nano–SiO2 (NS–NR2) was synthesized based on the 3–aminopropyltrimethoxysilane (KH540) modified nano–SiO2 (NS–NH2) via methylation. The chemical structure and performances of the NS–NR2 were characterized through a series of experiments, which revealed that NS–NR2 can react with CO2 in water and nanofluid with low viscosity revealed better CO2 capture. The CO2 capture mechanism of NS–NR2 was studied by kinetic models. From the correlation coefficient, the pseudo second order model was found to fit well with the experiment data. The influencing factors were investigated, including temperature, dispersants, and cycling numbers. Results has shown the additional surfactant to greatly promote the CO2 adsorption performance of NS–NR2 because of the better dispersity of nanoparticles. This work proved that NS–NR2 yields low viscosity, high capacity for CO2 capture, and good regenerability in water. NS–NR2 with high CO2 capture will play a role in storing CO2 to enhanced oil recovery in CO2 flooding.